The Code of Chaos - Wilderness, Language and the Circularity of Escape in Don DeLillo’s The Names - Guimarães, João Paulo (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
.